Influence of Aerobic Exercise on State and Trait Anxiety among Working Women in Malaysia: A Qualitative Study - Johar, Mastura; Latif, Rozita Abdul; Fauzee, Mohd Sofian Omar (EDUCARE, 2008)
ABSTRACT: Exercise is a beneficial and efficient way to improve oneâs health status. Numerous studies have looked at both the physiological and psychological health benefits of physical exercise, however, studies that examine the relationship between exercise and psychological health, specifically on anxiety, report ambiguous findings. This paper, a qualitative study, diminishes the ambiguity by explaining the relationship between aerobic exercise, trait anxiety, and state anxiety. Four female participants engaged in an aerobics exercise class in Bandar Baru Bangi, Selangor, Malaysia, they were all employed women working within the town. The participants ranged from 25 to 55 years of age, with an average age of 40. It was found that trait anxiety moderated the effect aerobic exercise had on a womanâs state anxiety level following aerobic exercise. Women with a higher level of trait anxiety reported a lower level of state anxiety following exercise when they participated in more hours of aerobic exercise per week. On the other hand, aerobic exercise had little effect on state anxiety levels in women with low trait anxiety levels.KEY WORDS: psychological health, state anxiety, trait anxiety, aerobic exercise, and women at work.Â Â Â Â About the Authors: Mastura Johar, M.A. is a lecturer of UNITEN (Universiti Tenaga Nasional); Rozita Abdul Latif, M.A. is a lecturer of UiTM (Universiti Teknologi MARA); and Prof. Madya Dr. Mohd Sofian Omar Fauzee is a lecturer of UPM (Universiti Putra Malaysia). One of them could be contacted at: mastura@uniten.edu.myHow to cite this article? Johar, Mastura, Rozita Abdul Latif & Mohd Sofian Omar Fauzee. (2008). âInfluence of Aerobic Exercise on State and Trait Anxiety among Working Women in Malaysia: A Qualitative Studyâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.67-80. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 21, 2008); Revised (July 25, 2008); and Published (August 17, 2008).